Identification and verification of the key genes involved in gallbladder cancer - Tang, Jie; Zhou, Hanxu; Lu, Miao; Cao, Dengyi; Zhang, Yun; Zhou, Shaobo (Frontiers in Immunology, 2025)
BackgroundGallbladder cancer (GBC) is a highly aggressive malignancy of the biliary tract. It often lacks distinct symptoms in its early stages, and no specific biomarkers have yet been identified for its diagnosis.ObjectiveTo identify key genes involved in GBC pathogenesis using public databases and bioinformatics analysis and validate these findings experimentally, providing a foundation for developing potential GBC biomarkers.MethodsAnalysis of GBC-related data from the Gene Expression Omnibus database revealed that G protein-coupled receptor 64 (GPR64) was differentially expressed in GBC. GPR64 expression in GBC-SD and NOZ cells was modulated using lentiviral transfection. Functional assays assessed cancer-related phenotypes, while apoptosis was measured using flow cytometry. Xenograft models in nude mice were established with cell lines overexpressing GPR64.ResultsGPR64 expression was reduced in GBC. Its overexpression suppressed GBC cell invasion, migration, and proliferation, and induced apoptosis. In vivo findings were consistent with in vitro results.ConclusionGPR64 plays a critical role in GBC pathogenesis and may serve as a promising biomarker for its diagnosis and treatment.